Analytically Modeling, Design and Analysis a Nonlinear Controller for a STATCOM operations - J. K. Moharana (IAES International Journal of Robotics and Automation (IJRA), 2018)
The concept of H Control is extended, in principle, to the SVPWM (Space Vector Pulse Width Modulation) based inverter switching of a STATCOM (STATic synchronous COMpensator) device. The SVPWM assures a greater value of modulation factor in the undermodulation as well as the overmodulation range compared to SPWM (Sine Pulse Width Modulation) i.e. a much higher fundamental content. In the present work, the STATCOM has been modeled and its model is nonlinear in  (phase angle between fundamental of system voltage and output voltage of STATCOM. The effect of increased modulation index and lower harmonic distortion has been studied through simulation w.r.t. different performance indices and dynamic response of relevant variables. A PI and an H Controller have been designed for closed-loop control of the system. It is found through simulation that H controller gives better response than PI controller for nonlinear system.